2020
DOI: 10.38136/jgon.768239
|View full text |Cite
|
Sign up to set email alerts
|

Az bilinen bir konu ‘Menstrüel Psikoz’: Bir olgu sunumu ve kısa bir gözden geçirme

Abstract: Menstrual psychosis (MP) is a condition that is associated with the menstrual cycle and can cause significant mental changes. Information about diagnosis and treatment approaches is limited. MP, which is generally reported to occur in young women around the age of 16, typically has an acute onset consistent with the premenstrual cycle, with short-term psychotic symptoms, and a clinical appearance that ends within a few days of discontinuation of menstruation bleeding. In addition to psychotic symptoms, patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…Aynalar örtülür, deri elbiseler giyilmez ve kadınlar bir ay boyunca makyaj yapmaz, erkekler de tıraş olmazlar. On bir ay sonra sembolik bir taşın kırılmasıyla yas sonlandırılır (Çolak ve Hocaoğlu, 2021). Yahudilikte yaygın olarak görülen diğer bazı yas adetleri içerisinde elbise yırtma, çula sarılma, üzerine kül serpme-kül üzerinde yatma, oruç tutma, saç-baş yolma ve dövünme yer almaktadır.…”
Section: Hristiyan Ve Yahudi Toplumlarında Cenaze Törenleri Ve Yasunclassified
“…Aynalar örtülür, deri elbiseler giyilmez ve kadınlar bir ay boyunca makyaj yapmaz, erkekler de tıraş olmazlar. On bir ay sonra sembolik bir taşın kırılmasıyla yas sonlandırılır (Çolak ve Hocaoğlu, 2021). Yahudilikte yaygın olarak görülen diğer bazı yas adetleri içerisinde elbise yırtma, çula sarılma, üzerine kül serpme-kül üzerinde yatma, oruç tutma, saç-baş yolma ve dövünme yer almaktadır.…”
Section: Hristiyan Ve Yahudi Toplumlarında Cenaze Törenleri Ve Yasunclassified
“…The differential susceptibility theory highlights the importance of environmental effects, so revealing the impact of the earthquake on preschool children may be beneficial. Also, numerous studies emphasize the vulnerability of children in the event of an earthquake (Çolak & Hocaoğlu, 2021;Özkan & Kutun, 2021;Takada, 2013). Some studies have shown that children tend to suffer more mental health issues than adults in the aftermath of natural disasters like earthquakes (Özkan & Kutun, 2021).…”
Section: Psychological Problemsmentioning
confidence: 99%
“…In this regard, Takada (2013) states that preschool children struggle to comprehend earthquakes and cannot deal with them effectively. Likewise, Çolak and Hocaoğlu (2021) express that preschool children cannot understand the deaths that occur around them. Children under magical thinking consider that the deceased can return.…”
Section: Psychological Problemsmentioning
confidence: 99%
See 1 more Smart Citation